2006
DOI: 10.1021/bi060204d
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization Specificity of Adult and Neonatal Chicken Skeletal Muscle Myosin Heavy Chain Rods

Abstract: The dimerization specificity of the recombinantly expressed and purified rod domain of adult and neonatal chicken myosin heavy chain was analyzed using metal chelation chromatography. Our results indicate that full-length adult and neonatal rods preferentially formed homodimers when renatured from an equimolar mixture of the two isoforms denatured in guanidine hydrochloride. The contribution made toward the dimerization specificity by subdomains of the rod has been addressed by making a chimeric protein consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Significant motility of eGFP-myosin fusions was also shown previously (Reisen and Hanson, 2007;Sparkes et al, 2008). Heterodimers of myosins were detected in low percentage in different systems; however, it was shown that homodimers are more thermodynamically stable (Dechesne et al, 1987;Kerwin and Bandman, 1991;Singh and Bandman, 2006), and heterodimerization of plant myosins is still to be tested. Interestingly, heterologous interaction between two subdomains of the globular tails GT1 from MYA1 and GT2 from MYA2, XI-C, or XI-K was observed in yeast two-hybrid analysis (Li and Nebenfü hr, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…Significant motility of eGFP-myosin fusions was also shown previously (Reisen and Hanson, 2007;Sparkes et al, 2008). Heterodimers of myosins were detected in low percentage in different systems; however, it was shown that homodimers are more thermodynamically stable (Dechesne et al, 1987;Kerwin and Bandman, 1991;Singh and Bandman, 2006), and heterodimerization of plant myosins is still to be tested. Interestingly, heterologous interaction between two subdomains of the globular tails GT1 from MYA1 and GT2 from MYA2, XI-C, or XI-K was observed in yeast two-hybrid analysis (Li and Nebenfü hr, 2007).…”
Section: Discussionsupporting
confidence: 66%
“…However, the tail [ 37 , 41 , 51 ] and coiled-coil fragments show little co-localization with actin. Another explanation could be that myosin tails of other isoforms form heterodimers with XI-K, similar to other systems [ 9 , 52 ]. However, heterodimers of myosins were only detected in low percentage in some systems and it was shown that homodimers are more thermodynamically stable [ 52 ], making it very unlikely that heterodimerization of non-functional dimers could cause a strong dominant negative effect.…”
Section: Discussionmentioning
confidence: 96%
“…Another explanation could be that myosin tails of other isoforms form heterodimers with XI-K, similar to other systems [ 9 , 52 ]. However, heterodimers of myosins were only detected in low percentage in some systems and it was shown that homodimers are more thermodynamically stable [ 52 ], making it very unlikely that heterodimerization of non-functional dimers could cause a strong dominant negative effect. Consistent with this, we show in this study that overexpression of coiled-coil domains has only a weak effect on P-body movement.…”
Section: Discussionmentioning
confidence: 96%
“…Because there was a corresponding decrease in endogenous MHC expression coincident with headless-MHC it is likely that the sarcomere of the transduced cardiac myocyte contained a population of single-headed dimeric MHC motor molecules. Because the headless-MHC construct contained the entire COOH-terminal rod domain, the most important domain for heavy chain assembly into the thick filament (22,29,30), motor domain truncation should not have impaired the ability of headless-MHC to dimerize with endogenous MHC and assemble into the thick filament. In this regard, the observation that headless-MHC expression was greatest 72-96 h after gene delivery while modest contractile deficits were observed at only at 96 h may relate to turnover rate for endogenous MHC (17) delaying actual replacement of endogenous MHC with headless-MHC relative.…”
Section: Discussionmentioning
confidence: 99%